Smart-technology in the asynchronic system of teaching english to smart medical students - Volkova, G. K.; Wieler, G. O.; Волкова, Галина Костянтинівна; Вілер, Ганна Олександрівна (Запоріжжя : КПУ, 2022)
The article is devoted to the problem of reconsidering approaches to the implementation of existing information technologies, analysis and evaluation of their use in the educational process in order to improve students' cognitive abilities, development of independence, self-affirmation of young people in acquiring and developing professional competencies in the 21st century. The article presents the purpose, objectives and content of Smart education in the Smart-society system, analyzes the features of organization of the educational process using SMART-technologies in foreign language classes in higher medical educational institutions. Nowadays, Smart-learning draws on and highly depends on the use of cloud technologies as well as a wide range of available modern programme applications and other additional options of virtual communication. Such efficient facilities enable young people to get proper education, realize their creative and intellectual potential within the framework of intermediated contact with a teacher and without a fixed place of training. Witnessing an onward and continual transfer from e-learning to Smart-learning the authors present their own experience in asynchronous learning process, as well as give recommendations for ensuring the practical focus and effectiveness of the educational process, increased motivation and engagement of young people in the learning process, implementation of various forms and types of educational activities in the English language for professional purposes classes with senior medical students. Introduction of innovative approaches, technologies and methods of work with foreign language material while its acquisition as well as developing engagingly original exercises are sure to enhance foreign language skills acquisition in this new paradigm of learning, which will definitely lead to formation of an efficient specialist who complies with the challenges of this new SMART époque. Smart students, in their turn, are sure to get satisfaction with their professional growth as well as comprehension of their readiness to work in the modern world of professional communication. Статтю присвячено проблемі переосмислення підходів до реалізації існуючих інформаційних технологій, аналізу і оцінки можливостей їхнього використання в навчальному процесі з метою підвищення когнітивних здібностей студентів, розвитку самостійності, самоствердження молоді під час набуття та розвитку професійних компетентностей. Перед освітянами постає завдання творчого переосмислення підходів до реалізації існуючих інформаційних технологій, аналізу й оцінки можливостей їхнього використання в навчальному процесі з метою підвищення когнітивних здібностей студентів та становлення самостійності та самоствердження молоді під час набуття та розвитку професійних компетентностей. У статті розкрито мету, завдання та зміст розумної (Smart) освіти у системі Smart-суспільства, проаналізовано особливості організації навчального процесу з використанням SMART-технологій на заняттях з іноземної мови у вищих медичних навчальних закладах. Авторами представлено власний досвід роботи в умовах асинхронного навчання, а також подано рекомендації щодо забезпечення практичної спрямованості та результативності навчального процесу; підвищеної мотивації молодих людей до процесу навчання; втілення різноманітних форм і видів навчальної діяльності на заняттях з англійської мови професійного спрямування зі студентами-медиками старших курсів. Організація курсу «Англійська мова професійного спрямування: просунутий рівень» у медичному університеті свідчить про те, що інформаційні технології у нашому сьогоденні повинні розглядатися як необхідний елемент навчального процесу. Навчальні посібники, складені на основі сучасних інформаційних матеріалів та укомплектовані інтерактивними вправами і комунікативними завданнями з урахуванням Smart-технологій і підходів, є потужним засобом навчання і сприяють розвитку творчої навчальної активності обох сторін навчального процесу. У свою чергу Smart-студенти отримують разом із задоволенням від власних досягнень у медичній англійській усвідомлення своєї професійної готовності до випробувань у всесвітньому просторі професійного і соціального спілкування.
Смарт-технології в асинхронному навчанні англійської мови smart студентів-медиків
Keywords: SMART-students; SMART-learning; asynchronic teaching; senior medical students; foreign languages acquisition; advanced level; professional competences; SMART-технології; SMART-студенти медичних вишів; розумна освіта; англійська мова за професійним спрямуванням; навчальний процес; професійні компетентності; просунутий рівень